Between a Rock and a Hard Place: Anticoagulating an Adolescent with Post-Tonsillectomy Massive PE: A Case Report. (March 2023) - Shimomura, Aoi; Smith, Sullivan; Darki, Amir; Kamberos, Natalie; Charous, Steven
Objectives: To report a case of a morbidly obese 17-year-old boy who presented 4 days post-tonsillectomy with acute deep venous thromboses and a massive pulmonary embolism. To describe a protocol and decision-making tree for providing anticoagulation in the immediate post-tonsillectomy period. Methods: A chart review and review of the literature. Results: The patient ultimately did well and had no bleeding from the tonsil beds or further thromboembolic complications. A review of the literature revealed no available data regarding the safety of anticoagulation in the immediate post-tonsillectomy period. Conclusions: We propose that if anticoagulation is needed within 14 days of tonsillectomy, submaximal anticoagulation with a reversible and titratable anticoagulant may be optimal. A multidisciplinary team approach is needed for these complex cases. Future reporting and investigation of anticoagulation post-tonsillectomy is needed.